(untitled) (Raparin Journal of Humanities (RJH), 2024)
The entry of modern technology into our society, particularly the emergence of the Internet with various sites that are easy to search, is one of youtube most important and popular sites, creating a new generation of children addicted to their use despite the large number of YouTube has become a real danger in the light of excessive use by children, however, it is ifficult to control the prevention of children from being exposed to the Internet in general and to YouTube videos in particular, many children in the developing stage of the disease. Psychological and neurological as a result of the content presented to them via video. The aim of this research is the role of YouTube videos on children’s belligerent behavior at the age of 2-6 for this 200 forms on mothers in the city border Rania was divided into 100 male and 100 female children, for example. It was later revealed that children are most likely to be YouTube users at a high rate and that mothers don’t monitor their children at the time you’ve seen YouTube and the degree of aggressive behavior that has changed according to gender, which is more likely to be male than female.